2021
DOI: 10.21203/rs.3.rs-149285/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Usefulness of Virtual Reality-Based Training to Diagnose Strabismus

Abstract: Purpose: To study the usefulness of virtual reality (VR) based training for diagnosing strabismusMethods: Fourteen ophthalmology residents performed at least 30 VR training sessions to diagnose esotropia and exotropia. Examinations of real patients with esotropia or exotropia before and after the VR training were video-recorded and presented to a strabismus expert to assess accuracy and performance scores for measuring the deviation angle and diagnosing strabismus with anonymization. A feedback survey regardin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…VR and AR have been explored in many aspects in ophthalmologic and optometric fields, such as low vision [13], glaucoma [14,15], strabismus [16,17], testing binocular imbalance [18,19], age-related macular degeneration [20], and distance-based vision aid for blind [13]. Several studies aimed to train amblyopia based on VR technology and showed various improvement in visual acuity.…”
Section: Introductionmentioning
confidence: 99%
“…VR and AR have been explored in many aspects in ophthalmologic and optometric fields, such as low vision [13], glaucoma [14,15], strabismus [16,17], testing binocular imbalance [18,19], age-related macular degeneration [20], and distance-based vision aid for blind [13]. Several studies aimed to train amblyopia based on VR technology and showed various improvement in visual acuity.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is possible to build a scene, perform the covering test through AI, and retain the image data for the automatic diagnosis of strabismus. VR technology gives the human eye a sense of three-dimensionality through binocular parallax, which allows the construction of a scene for looking near and far [10] , combined with an infrared camera to capture the eye movement data, an AI simulation of the covering test, and nally, the use of an AI image processing algorithm for diagnosing strabismus and calculating strabismic angle, which solves the problem of the shortage of clinical strabismus specialist and the problem of long examination time.…”
Section: Discussionmentioning
confidence: 99%
“…The skill and experience of the examiner play an important role, as well as factors such as the psychophysical state of the examiner and patient, the time of day or coexisting diseases, such as developmental disabilities (18). The difficulty of the performed tests, and the role of the examiner's experience is evidenced by the development of a virtual reality strabismus angle assessment training application, the use of which significantly improves the examiner's accuracy and efficiency (19).…”
Section: Evaluation By Conventional Methodsmentioning
confidence: 99%